Dynamics of longitudinal dentate gyrus axons associated with seizure. (22nd March 2021) - Choi, Gona; Kang, Hyeri; Chu, Wenkei; Yang, Sunggu; Yang, Sungchil
Abstract : Key points: Axon collaterals of DG granule neurons project towards neighbouring DG granule cell layer Longitudinal axons in the DG‐DG circuit possess denser synapses than transverse axons in the DG‐CA3 circuit The size of varicosities of the longitudinal axons, but not transverse ones, is regulated by seizures as measured behaviourally Varicosity size of DG‐DG axons can be a symptomatic marker of DG‐related brain diseases Abstract: The hippocampus network has captured the attention of neuroscientists as a model for understanding cognition and behaviour. Previously, we have identified interlamellar, namely longitudinal, axons between CA1 pyramidal neurons analogous to recurrent connections between CA3 pyramidal neurons. Currently it is unknown whether longitudinal axons of DG granule neurons are present and how they are associated with the behavioural symptoms of seizure. We found longitudinal axons projections from DG granule cells extending to neighbouring DG granule cell layers. These DG‐DG axons have more numerous varicosities and are thinner than the DG‐CA3 axons, suggesting heavy synaptic formation along a longitudinal axis. Furthermore, the size of varicosities in the DG‐DG but not DG‐CA3 axons is regulated by seizures as measured behaviourally. The results suggest that the dynamics of longitudinal DG axons is a symptomatic marker of DG‐related brain diseases. Key points: Axon collaterals of DG granule neurons project towards neighbouring DG granule cell layer Longitudinal axons in the DG‐DG circuit possess denser synapses than transverse axons in the DG‐CA3 circuit The size of varicosities of the longitudinal axons, but not transverse ones, is regulated by seizures as measured behaviourally Varicosity size of DG‐DG axons can be a symptomatic marker of DG‐related brain diseases